The Role of Small Heterodimer Partner (SHP) in NAFLD Improvement after Vertical Sleeve Gastrectomy in Mice - Myronovych, Andriy (Obesity (Silver Spring), 2014)
OBJECTIVE: Bile acids (BA) are elevated after vertical sleeve gastrectomy (VSG) and farnesoid-X-receptor (FXR) is critical to the success of murine VSG. BA down-regulate hepatic lipogenesis by activating the FXR-small heterodimer partner (SHP) pathway. We tested the role of SHP in fatty liver disease (NAFLD) improvement after VSG. DESIGN AND METHODS: Wild type (WT), SHP liver-transgenic (SHP-Tg) and SHP knockout (SHP-KO) high-fat diet (HFD) fed mice underwent either VSG or Sham surgery. Body weight, BA level & composition, steatosis and BA metabolism gene expression were evaluated. RESULTS: Obese WT mice post-VSG lost weight, reduced steatosis, decreased plasma alanine aminotransferase (ALT), had more BA absorptive ileal area, and elevated serum BA. Obese SHP-Tg mice post-VSG also lost weight and had decreased steatosis. SHP-KO mice were however resistant to steatosis despite weight gain on a HFD. Further SHP-KO mice that underwent VSG lost weight but developed hepatic inflammation and had increased ALT. CONCLUSIONS: VSG produces weight loss independent of SHP status. SHP ablation creates a pro-inflammatory phenotype which is exacerbated after VSG despite weight loss. These inflammatory alterations are possibly related to factors extrinsic to a direct manifestation of NASH.